(untitled) (JURNAL IBU DAN ANAK, 2022)
adequated nutrition. Severals attempts were made to achieve exclusive breastfeeding, like education about breastfeeding, support, and confidence of mother. It is contained in a model called tri core breastfeeding model which is a practice guideline in the form of health promotion are given to mothers in breastfeeding. The purpose of this research was to determine the effect of tri core breastfeeding models on the willingness of nursing mothers. This research was conducted at PMB hasna dewi pekanbaru in august 2019 until april 2020. The type of research was preeksperimental design. Population in this study were all tri semester pregnant women at PMB hasna dewi in pekanbaru since January to april 2020. A sample was 20 pregnant woment were taken by consecutive sampling technique. The method of collecting data using infant feeding intention scale (IFI) questionnaire. Data analysis using independent T test with a significance level of 95%. There was a difference in breastfeeding willingness in the intervenetion group and the control group (p= 0,017) suggested tri core breastfeeding models can be applied in providing midwifery care that can support the success of exclusive breastfeeding.